2020
DOI: 10.3390/w12020318
|View full text |Cite
|
Sign up to set email alerts
|

13 Years of Storms: An Analysis of the Effects of Storms on Lake Physics on the Atlantic Fringe of Europe

Abstract: While winter storms are generally common in western Europe, the rarer summer storms may result in more pronounced impacts on lake physics. Using long-term, high frequency datasets of weather and lake thermal structure from the west of Ireland (2005 to 2017), we quantified the effects of storms on the physical conditions in a monomictic, deep lake close to the Atlantic Ocean. We analysed a total of 227 storms during the stratified (May to September, n = 51) and non-stratified (November to March, n = 176) period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 54 publications
1
17
0
Order By: Relevance
“…Such reasoning is supported by the greater decrease in PSD 5-95 (which is related to temperature changes) in shallower vs. deeper lakes. Similar storm-induced changes in Schmidt stability was found in previous studies conducted on three of the lakes in our dataset (Feeagh: Andersen et al 2020;Calderó-Pascual et al 2020;Feeagh, Erken, and Müggelsee: Mesman et al 2020). Internal seiches, upwelling, and internal waves breaking on the shores can also mix colder hypolimnetic water with the warmer epilimnetic water from storms in deeper lakes (i.e., Kirillin and Shatwell 2016;Kasprzak et al 2017).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Such reasoning is supported by the greater decrease in PSD 5-95 (which is related to temperature changes) in shallower vs. deeper lakes. Similar storm-induced changes in Schmidt stability was found in previous studies conducted on three of the lakes in our dataset (Feeagh: Andersen et al 2020;Calderó-Pascual et al 2020;Feeagh, Erken, and Müggelsee: Mesman et al 2020). Internal seiches, upwelling, and internal waves breaking on the shores can also mix colder hypolimnetic water with the warmer epilimnetic water from storms in deeper lakes (i.e., Kirillin and Shatwell 2016;Kasprzak et al 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Other ways exist to quantify a storm and impacts of a storm on lake conditions. For example, Andersen et al (2020) defined a storm as conditions 1 d after the storm ( t + 1) compared to conditions 1 d before a storm ( t − 1). We tested the robustness of our estimates of mean ETD 5‐95 from wind and rainstorms using this alternative method.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extreme weather events are common in the west of Ireland. A recent 13-year study of Lough Feeagh by Andersen et al (2020) [31] found that, on average, there were four storms per year at Lough Feeagh during the stratified period (May-September), with at least one storm occurring every year. It was also notable that the threshold wind speed value (top 2.5%) for a storm at this coastal site was 10.6 m s −1 , much higher than that reported for example in mainland Europe [32].…”
Section: Introductionmentioning
confidence: 99%